Correlation of prefrontal cortical activation with changing vehicle speeds in actual driving: a vector-based functional near-infrared spectroscopy study - Yoshino, Kayoko; Oka, Noriyuki; Yamamoto, Kouji; Takahashi, Hideki; Kato, Toshinori (Frontiers in Human Neuroscience, 2013)
Traffic accidents occur more frequently during deceleration than during acceleration. However, little is known about the relationship between brain activation and vehicle acceleration because it has been difficult to measure the brain activation of drivers while they drive. In this study, we measured brain activation during actual driving using vector-based functional near-infrared spectroscopy. Subjects decelerated from 100 to 50 km/h (speed reduction task) and accelerated from 50 to 100 km/h (speed increase task) while driving on an expressway, in the daytime and at night. We examined correlations between average vehicle acceleration in each task and five hemodynamic indices: changes in oxygenated hemoglobin (ΔoxyHb), deoxygenated hemoglobin (ΔdeoxyHb), cerebral blood volume (ΔCBV), and cerebral oxygen exchange (ΔCOE); and the phase angle k (degrees) derived from the other hemoglobin (Hb) indices. ΔoxyHb and ΔCBV reflect changes in cerebral blood flow, whereas ΔdeoxyHb, ΔCOE, and k are related to variations in cerebral oxygen metabolism. Most of the resulting correlations with specific brain sites, for all the indices, appeared during deceleration rather than during acceleration. Faster deceleration resulted in greater increases in ΔdeoxyHb, ΔCOE, and k in the prefrontal cortex (r < −0.5, p < 0.01), in particular, in the frontal eye field, and at night, it also resulted in greater decreases in ΔoxyHb and ΔCBV in the prefrontal cortex and in the parietal lobe (r > 0.4, p < 0.01), suggesting oxygen metabolism associated with transient ischemic changes. Our results suggest that vehicle deceleration requires more brain activation, focused in the prefrontal cortex, than does acceleration. From the standpoint of the indices used, we found that simultaneous analysis of multiple hemodynamic indices was able to detect not only the blood flow components of hemodynamic responses, but also more localized frontal lobe activation involving oxygen metabolism.